Mergers and Birth Outcomes: Evidence from Maternity Ward Closures - Daniel Avdic; Petter Lundborg; Johan Vikström (Institute of Labor Economics (IZA), 2018)
Evidence suggests that hospital mergers can reduce costs but less is known about their effects on patient outcomes. We study how a wave of mergers that led to the shutdown of one third of all Swedish maternity wards affected the health of mothers who gave birth and their newborns. Applying a difference-in-differences approach to register data on all births in Sweden over two decades, we show that the closures negatively affected the health of mothers, while effects on infant health were small and insignificant. The adverse effects on mothers are mainly driven by crowding effects at remaining wards rather than by increased distance to the wards. Moreover, the closures reduced the use of C-sections for high-risk births.
Keywords: D24; I11; I18; J13; R41; 330; quality of care; hospital closure; birth outcomes